2021
DOI: 10.7717/peerj.11117
|View full text |Cite
|
Sign up to set email alerts
|

Multi-schema computational prediction of the comprehensive SARS-CoV-2 vs. human interactome

Abstract: Background Understanding the disease pathogenesis of the novel coronavirus, denoted SARS-CoV-2, is critical to the development of anti-SARS-CoV-2 therapeutics. The global propagation of the viral disease, denoted COVID-19 (“coronavirus disease 2019”), has unified the scientific community in searching for possible inhibitory small molecules or polypeptides. A holistic understanding of the SARS-CoV-2 vs. human inter-species interactome promises to identify putative protein-protein interactions (PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…numerical mapping models), but to leverage the context enabled by transfer learning these DTA measures (i.e. CM-RP), promises exciting results given that the application of RP to related bioinformatic problems has led to statistically significant improvements of predictor performance 42 , 43 , 48 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…numerical mapping models), but to leverage the context enabled by transfer learning these DTA measures (i.e. CM-RP), promises exciting results given that the application of RP to related bioinformatic problems has led to statistically significant improvements of predictor performance 42 , 43 , 48 .…”
Section: Resultsmentioning
confidence: 99%
“…Prior DTI literature suggests that the incorporation of individual DTI predictors into an ensemble will outperform those individual models 50 . The work of Dick et al on predicting protein-protein interactions (PPI) between SARS-CoV-2 and humans demonstrated that RP could be used to ensemble two PPI predictors (the Protein-protein Interaction Prediction Engine [PIPE4] 51 and the Scoring PRotein INTeractions [SPRINT] 52 models) to produce an RP fusion model 48 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations